(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2020)
The Foreign Account Tax Compliance Act (FATCA) basically targets US citizens’ accounts hold at foreign banks and financial institutions blush, seems and non-financial sector by the Act:( retirement plan companies, investment funds, hedge funds and family investment companies.) The non Compliance of Foreign of financial institutions act will lead to financial looses and harm regarding reputation, especially for the countries that rely on foreign relations in their financial and banking activities, in addition to deducting 30 % of their total incomes and sales coming from the USA. These institutions can avoid it by entering into agreement with the Internal Revenue Service’s to be foreign financial institutions complied with the act. The Iraqi Government entered into a god-will agreement in this connection with the US side according to Model (2) of FATCA , to enhance Iraq’s reputation worldwide, especially regarding world banking sector. Thus, all financial institutions and banks of Iraq become complied with the Act according to the US-Iraq Inter-Government Agreement. Iraqi financial institutions sought at signing up for the Internal Revenue Service’s gaining a (GIIN) and complying with the Act, to assure compliance with the Central Bank of Iraq’s local laws of Act enforcement. Research dilemma is considering how potential the Iraqi banking sector of putting the Foreign Account Tax Compliance Act (FATCA) Through The Specialized Computerized Program in place and reporting to the Internal Revenue Services . Therefore, the research seeks at knowing what the Foreign Account Tax Compliance Act (FATCA) is about and considering how capable the Iraqi Banking Sector of enforcement of the Act. To achieve this goal researcher hypothesis has provided that: The Iraqi banking sector is able to comply with the application for the foreign accounts tax compliance Act (FATCA) and implementation of the basic requirements of the law through the specialized computerized program for the purpose of preparation and sending financial reports on US persons subject to the Act and are intended to be disclosed to the Department US internal revenue Service .